(untitled) (Palíndromo, 2023)
The following text is the result of an interview with Brazilian artist and professor Edith Derdyk, which focused on the relationship between artists’ publications and the artistic and pedagogical process. In addition to these main themes, the artist describes part of her creative and poetic process, revealing some of her philosophical, theoretical, and artistic influences. Even when working with different materials and mediums, she emphasizes that the guiding thread of her poetics is the "line," which takes the form of drawing, writing, artist’s books, sculpture, installation, or even the physical movement of the artist’s own body.